Pengaruh Kompetensi, Disiplin Kerja Dan Lingkungan Kerja Fisik Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Pemediasi - Gushar Driani Sundari; Eka Risma Putri (STIE AMKOP, 2023)
This study aims to analyze the effect of competence, work discipline and physical work environment on employee performance with job satisfaction as mediation. This research is motivated by problems in employee performance caused by problems with employee competence that still have to be improved, employee work discipline that is still low, the physical work environment that is still perceived as less supportive at work and the level of employee job satisfaction that is still problematic in the Regional Finance Agency of Pasaman Regency. This type of research is quantitative using the Partial Least Square approach with the Structural Equation Modeling equation model. Data collection by questionnaire and observation. Research respondents totaled 61 civil servants at the Regional Finance Agency of Pasaman Regency. The sampling method uses total sampling where the entire research population is sampled. Hypothesis testing using the SmartPLS program. The results of this study found that in the direct effect competence has no positive and significant effect on performance, work discipline and physical work environment have a positive and significant effect on performance, job satisfaction and competence have no positive and significant effect on job satisfaction, work discipline and physical work environment have a positive and significant effect on job satisfaction. While the indirect effect found that job satisfaction does not mediate the relationship between competence and performance, the relationship between work discipline and performance and the relationship between the physical work environment and the performance of Civil Servants at the Regional Finance Agency of Pasaman Regency. Keywords: Competence, Work Discipline, Physical Work Environment, Job Satisfaction, Performance